Design of Hybrid Koch-Minkowski fractal dipole antenna for dual band wireless applications - Abdul Malek, Norun; Che Sabri, Nur Alyaa; Islam, Md. Rafiqul; Mohamad, Sarah Yasmin; Mohd. Isa, Farah Nadia (2019)
— In many wireless applications, antenna comes with variable sizes. The interest for small and compact antennas in wireless applications is increasing due to the mobility of the wireless devices. Internet of Things (IoT) defined as a network of small, low cost, low power, ubiquitous electronic devices. It is expected that WiFi proves to be one of the solutions for IoT technology. WiFi Alliance has introduced an unlicensed band of 900 MHz (HaLow) in 2017 to support IoT which requires low power, high data rate and long range. Hence, the demand for small antennas is substantial especially due to the booming industry in mobile communication. Generally, an antenna at low frequency exhibits large size of antenna. This paper presents the design of fractal dipole antennas for dual band wireless applications. The designs are based on hybrid Koch-Minkowski fractal method for the benefits of miniaturization. The antenna designs have been simulated using CST Microwave Studio and fabricated using Rogers 5880 substrate. Based on the results, it is observed that the fractal antennas are able to operate at dual frequencies, at 900 MHz and 2.6 GHz with return loss of 18dB and 16 dB respectively. The small size, thin and lightweight of antenna design (115 mm x 22.5 mm x 0.285 mm) makes it an attractive feature for compact wireless applications.